Clinical Significance and Immune Landscape of a Pyroptosis-Derived LncRNA Signature for Glioblastoma - Xing, Zhe; Liu, Zaoqu; Fu, Xudong; Zhou, Shaolong; Liu, Long; Dang, Qin; Guo, Chunguang; Ge, Xiaoyong; Lu, Taoyuan; Zheng, Youyang; Dai, Lirui; Han, Xinwei; et al. (Frontiers in Cell and Developmental Biology, 2022)
Abstract Introduction: Pyroptosis was recently implicated in the initiation and progression of tumors, including glioblastoma (GBM). This study aimed to explore the clinical significance of pyroptosis-related lncRNAs (PRLs) in GBM. Methods: Three independent cohorts were retrieved from the TCGA and CGGA databases. The consensus clustering and weighted gene co-expression network analysis (WGCNA) was applied to identify PRLs. The LASSO algorithm was employed to develop and validate a pyroptosis-related lncRNA signature (PRLS) in three independent cohorts. The molecular characteristics, clinical significances, tumor microenvironment, immune checkpoints profiles, and benefits of chemotherapy and immunotherapy regarding to PRLS were also explored. Results: In the WGCNA framework, a key module that highly correlated with pyroptosis was extracted for identifying PRLs. Univariate Cox analysis further revealed the associations between PRLs and overall survival. Based on the expression profiles of PRLs, the PRLS was initially developed in TCGA cohort (n =143), and then validated in two CGGA cohorts (n =374). Multivariate Cox analysis demonstrated that our PRLS model was an independent risk factor. More importantly, this signature displayed the stable and accurate performance in predicting prognosis at 1, 3, and 5 years, with all AUCs were above 0.7. The decision curve analysis also indicated that our signature had promising clinical application. In addition, patients with high PRLS score suggested the more abundant immune infiltration, higher expression of immune checkpoint genes, and better response to immunotherapy but worse to chemotherapy. Conclusion: A novel pyroptosis-related lncRNA signature with the robust performance was constructed and validated in multiple cohorts. This signature provided new perspectives for clinical management and precise treatments of GBM.